PENGARUH DEEP BACK MASSAGE TERHADAP INTENSITAS NYERI PERSALINAN PADA IBU INPARTU KALA I FASE AKTIF: LAPORAN KASUS BERBASIS BUKTI (Politeknik Kesehatan Kemenkes Bandung, 2023)
Pain in labor is a manifestation of uterine muscle contractions. Labor pain can be stressful, causing excessive release of hormones such as catecholamines and steroids, which can directly affect uterine contractions and indirectly affect fetal conditions. Current complementary therapies such as massage in labor are proven to reduce pain and reduce the use of drugs in labor. The purpose of writing this EBCR is to apply the best evidence of Deep breathing in reducing pain in the first stage of labor. The search engines used for searching related journals are PubMed and Science direct, using the keywords childbirth / labor / deep back massage / pain labor which are then sorted according to the year of publication with a minimum of publication in the last 5 years and determining the level of evidence base of a journal thus 2 articles were selected. Results: there were significant pain scale differences before the massage and after the massage. Before the application of deep massage the pain scale was 7 and reduced to 5 after the application of deep massage. These results showed that there was an effect of deep back massage on pain during the first stage of the active phase. Conclusion: The deep back massage method can reduce labor pain during the active phase 1 because the smooth and soft touch of the massage can stimulate the body to release endorphin hormone which makes the mother more relaxed and comfortable. Therefore, the deep back massage method can be an alternative in reducing pain during labor.